ROLE OF QUALITY INDICATORS IN HAEMATOLOGY AND CLINICAL PATHOLOGY LABORATORY - DR. JYOTI PRAKASH SAPRE,; DR. SANJAY N CHAUDHARI, (International Journal of Pharma and Bio Sciences, 2015)
Quality indicators are measurement tools, screens or flags that are used as guides to monitor, evaluate and improve the quality of patient care, clinical support services and organizational function that affect patient outcomes. The goal of this study was to design and review quality indicators from time to time in an effort to improve the performance of the laboratory. Observational study done at Pramukhswami Medical College, Shree Krishna Hospital, Karamsad from January 2011 to December 2013. The study was conducted at Haematology and Clinical Pathology section of Central Diagnostic Laboratory, Shreekrishna Hospital, Karamsad during January 2011 to December 2013. Total 08 quality indicators were studied. The target for each quality indicator was set according to previous year’s performance. Total 1,43,106 samples were received. Quality indicators like internal quality control, external quality assessment, critical alerts, turnaround time, specimen collection & storage, completeness of requisition form, specimen rejection and avoidance of transcriptional error in reporting from log book to computer were studied and showed continuous quality improvement.Quality improvement plan in haematology and clinical pathology is an effective tool for ensuring continuous quality improvement by the use of quality indicators.